1986
DOI: 10.1126/science.3487117
|View full text |Cite
|
Sign up to set email alerts
|

Aminoguanidine Prevents Diabetes-Induced Arterial Wall Protein Cross-Linking

Abstract: Age-associated increases in collagen cross-linking and accumulation of advanced glycosylation products are both accelerated by diabetes, suggesting that glucose-derived cross-link formation may contribute to the development of chronic diabetic complications as well as certain physical changes of aging. Aminoguanidine, a nucleophilic hydrazine compound, prevented both the formation of fluorescent advanced nonenzymatic glycosylation products and the formation of glucose-derived collagen cross-links in vitro. Ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
623
3
12

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,122 publications
(650 citation statements)
references
References 28 publications
12
623
3
12
Order By: Relevance
“…Numerous studies have demonstrated that aminoguanidine is an inhibitor of many manifestations of nonenzymatic glycation (28,45,60,61), and it recently entered second phase III clinical trials for ameliorating the complications of diabetes (11,61). Our recent kinetic studies confirmed that aminoguanidine is a potent inhibitor of antigenic AGE formation induced by high glucose concentrations (44).…”
Section: Discussionsupporting
confidence: 56%
“…Numerous studies have demonstrated that aminoguanidine is an inhibitor of many manifestations of nonenzymatic glycation (28,45,60,61), and it recently entered second phase III clinical trials for ameliorating the complications of diabetes (11,61). Our recent kinetic studies confirmed that aminoguanidine is a potent inhibitor of antigenic AGE formation induced by high glucose concentrations (44).…”
Section: Discussionsupporting
confidence: 56%
“…2d). Second, we used aminoguanidine, which prevents the formation of AGE [27]. Prolonged incubation of apoA-I with aminoguanidine enhanced the ability of apoA-I to promote cholesterol efflux; however, cholesterol efflux was similar for apoA-I and apoA-I modified in the presence of aminoguanidine (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The recognition of NEG as a molecular mechanism that contributes to the development of OA provides new opportunities for therapies directed at the prevention of OA by inhibiting or reversing AGE formation. Inhibition of AGE formation by prophylactic treatment with compounds such as aminoguanidine, pyridoxamine, tenilsetam, or simple amino acids (e.g., lysine or arginine) has been shown to prevent AGErelated pathologies such as vascular stiffening, heart collagen accumulation, and protein crosslinking (59)(60)(61)(62)(63). Alternatively, AGE-directed therapy can consist of so-called AGE-breakers (64).…”
Section: Discussionmentioning
confidence: 99%